NATO at 70. Issue 2 (7th February 2019) - Unknown
Abstract : As NATO marks its 70th anniversary, it can celebrate increased investment, revitalised exercises and a sense of renewed purpose. Yet it remains vulnerable to numerous internal and external challenges. Its greatest immediate challenge is a US president who has reportedly considered withdrawing his country from the alliance.